Discourse Of Islamization In Indonesia: Hoesein Djajadiningrat’s Vision In The Colonial And Postcolonial Periods - Mohammad Refi Omar Ar Razy; Kunto Sofianto; Gani Ahmad Jaelani (Criksetra: Jurnal Pendidikan Sejarah, 2023)
Discourses on Islamization in Indonesia are quite varied, including giving birth to the opinion that Islam originated in Gujarat, Mecca, Persia and China. The problem is, the discourse about the opinion of the coming of Islam to Indonesia which later became a unified historical story is rarely found. The discourse on Islamization became a long discourse in the colonial and postcolonial periods. This paper aims to elaborate on the vision of Islamization according to Hoesein Djajadiningrat. Hoesein argues that Islam in Indonesia originates from Persia. The argument in this paper is that Hoesein as an intellectual can be aligned with scholars who give opinions on Islamization such as Snouck Hurgronje, Pijnappel, JP Moquette, Hamka, and Abu Bakar Aceh. This paper uses historical methods consisting of heuristics, criticism, interpretation, and historiography. The results in this paper find that the Islamization discourse originating from Persia is a strengthening of the Islamization of Gujarat and a counter discourse of Arab Islamization. Therefore, this paper will analyze, first, the Islamization Debate in Western discourse. Second, the postcolonial Islamization Debate, and Third, the Arab vs Persian Islamization debate.